PEMBERDAYAAN SANTRI PONDOK PESANTREN AL MUBARAK SUDIANG DALAM PEMBUDIDAYAAN DAN PEMANFAATAN TANAMAN OBAT - Kamaruddin, Mudyawati (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
Al Mubarak Sudiang Islamic Boarding School in Pai sub-district, Biringkanaya sub-district, Makassar is a semi-modern Islamic boarding school that combines Islamic religious knowledge with special skills (such as brick making and gardening) in its environment. Al Mubarak Sudiang Islamic Boarding School is located about 18 kilometers from Makassar. The acquisition of medicinal plant gardens at Al Mubarak Sudiang Islamic Boarding School is a good solution proposed by the team proposing community service activities; additionally, there is still sufficient land available, adequate human resources, climate support, and fertile soil owned by Al Mubarak Sudiang Islamic Boarding School, which can aid in the establishment of a medicinal plant garden. Counseling, demonstration, training, coaching, and mentoring are the methods used for implementation. The goals are to increase Al Mubarak Sudiang Islamic Boarding School students' knowledge of medicinal plant types, increase knowledge and understanding of the health benefits of medicinal plants, improve skills in cultivating medicinal plants, and improve health.